Diverse Intrinsic Properties Shape Functional Phenotype of Low-Frequency Neurons in the Auditory Brainstem - Hong, Hui; Wang, Xiaoyu; Lu, Ting; Zorio, Diego A. R.; Wang, Yuan; Sanchez, Jason Tait (Frontiers in Cellular Neuroscience, 2018)
In the auditory system, tonotopy is the spatial arrangement of where sounds of different frequencies are processed. Defined by the organization of neurons and their inputs, tonotopy emphasizes distinctions in neuronal structure and function across topographic gradients and is a common feature shared among vertebrates. In this study we characterized action potential firing patterns and ion channel properties from neurons located in the extremely low-frequency region of the chicken nucleus magnocellularis (NM), an auditory brainstem structure. We found that NM neurons responsible for encoding the lowest sound frequencies (termed NMc neurons) have enhanced excitability and fired bursts of action potentials to sinusoidal inputs ≤10 Hz; a distinct firing pattern compared to higher-frequency neurons. This response property was due to lower amounts of voltage dependent potassium (KV) conductances, unique combination of KV subunits and specialized sodium (NaV) channel properties. Particularly, NMc neurons had significantly lower KV1 and KV3 currents, but higher KV2 current. NMc neurons also showed larger and faster transient NaV current (INaT) with different voltage dependence of inactivation from higher-frequency neurons. In contrast, significantly smaller resurgent sodium current (INaR) was present in NMc with kinetics and voltage dependence that differed from higher-frequency neurons. Immunohistochemistry showed expression of NaV1.6 channel subtypes across the tonotopic axis. However, various immunoreactive patterns were observed between regions, likely underlying some tonotopic differences in INaT and INaR. Finally, using pharmacology and computational modeling, we concluded that KV3, KV2 channels and INaR work synergistically to regulate burst firing in NMc.